Knowing the hay from the needle: Yeast two-hybrid screens in Aspergillus nidulans - a set of clones to identify common "false positives". - L Hamer (Fungal Genetics Reports, 1998)
With the purpose of examining interacting components of the septation process in Aspergillus nidulans, a yeast two-hybrid library of A. nidulans hyphal cDNA has been constructed. The yeast interaction trap is based on the in vivo detection of heterologous protein-protein interactions that will activate transcription in Saccharomyces cerevisiae (bakers yeast). Although the system potentially is powerful, much effort is necessary to identify background interactors due to heterologous complementation and non-specific initiation of transcription. A set of "false positives" was identified, which can be used to reduce the background in future yeast two-hybrid screens of A. nidulans libraries.